З історії збирання, систематизації та видання чеських прислів’їв і приказок - Даниленко, Л. (Народна творчість та етнографія, 2008)
Exploring the old Czech culture, the author of the article addresses to that its layer, where the first shoots of the Czech proverbs and sayings appeared. L. Danylenko considers the chronicles and separate artistic works as the first kind of these word expressions. Lexicographic works which specially consisted as collections of proverbs and sayings belong to the second one. It is possible to judge about existence of the proverbs, sayings, by-words, sentences in Czech lands in time of bloom of dark ages (14th century) only on the basis of those specimen, which were fixed by the then written language, or those that were saved in memory of people and were borne to labours of more late times.